From Pergamon to Sperlonga : sculpture and context - De Grummond, Nancy Thomson; Ridgway, Brunilde Sismondo, 1929- (Hellenistic culture and society, 2000)
"This volume brings together the work of leading scholars on two of the most important yet puzzling extant ensembles of Hellenistic Age sculpture: the Great Altar at Pergamon, with its Gigantomachy and scenes from the life of Telephos, and the Cave at Sperlonga in Italy, with its epic themes connected especially with the adventures of Odysseus. From Pergamon to Sperlonga has three aims: to update the scholarship on two important monuments of ancient art and architecture; to debate questions of iconography, authorship, and date; and to broaden the scope of discussion on these monuments beyond the boundaries of studies done in the past. In addition, it brings forward new ideas about how these two monuments are connected and discusses possible means by which stylistic influences were transmitted between them." "The essays explore the historical and iconographic influences that produced some of the motifs and styles evident at both sites. They discuss Pergamene politics and victory dedications, suggest non-Greek antecedents and Roman developments of the Altar's scenography, and bring to bear Etruscan and Roman evidence on an analysis of the Sperlonga groups. The contributors explore and critique currently held opinions concerning these monuments and reach some novel conclusions that will demand that we take a fresh look at these famous works of art." "Together, this collection of essays is unique in that it treats difficult issues in Hellenistic, Etruscan, and Roman art and culture together in one volume, providing a stimulating and controversial look back to the Hellenistic Age."--Jacket.